PEMBUATAN SERBUK WEDANG REMPAH SEBAGAI PENINGKAT IMUN TUBUH BAGI ATLIT ATLETIK - Amrozi Khamidi; Edy Mintarto; Sri Usodoningtyas. (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2021)
Facing the new normal era of the Covid 19 outbreak, people are returning to activities like before the Covid 19 outbreak, amid the transmission of the Covid outbreak which is still quite high, all people are required to be able to keep their distance and transmission of firus covid 19 which is transmitted through dropled. Athletes who return to training must also maintain a healthy body, one of which is always maintaining immunity. Spices powder has been researched to increase immunity, so in this session the team is trying to make red ginger powder product and temu lawak ready to be brewed as a healthy drink to increase body immunity. This study uses a qualitative research type that digs up data in accordance with the facts that occur in the field with the method of collecting data through interviews, observation and documentation to get the results of community service about making spices powder as an immune booster for athletic athletes. The results of this service obtained data before the implementation of this PKM, athletes and athletic trainers had already consumed ginger, turmeric and ginger wedang, what distinguishes the wedang they usually consume is ginger / turmeric / curcuma which is crushed / hit instead of powder as produced. This PKM. According to athletes and athletic trainers, the benefits of ginger / turmeric / ginger spices are to warm the body and increase appetite.